STRATEGI PENGUATAN LITERASI DIGITAL BERBASIS KOMUNITAS DALAM PENGAWASAN PILKADA DI KALIMANTAN BARAT - Syarifah Ema Rahmaniah; Jumadi Jumadi; Annisa Rizqa Alamri (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2022)
Prevention of violations can be used by increasing coordination and institutional cooperation by seeking synergies and also collaborative roles among stakeholders. This study aims to conduct a critical study of the conventional communication sovereignty model and attempt to reconstruct the importance of the community based communication sovereignty model, related to the importance of the community media with effort to build communication sovereignty in participatory election. This research uses descriptive qualitative. Data were obtained through indepth interviews, observation and literature study. Then the data analized with rationally based on certain logical. The result of this research found, 1) Monitoring Participatory election means public awareness and participation by monitoring the implementation of the election. 2) Conducting a study on election issues will help to prevent the violations. 3) Submitting information on alleged election violations and support the compliance of election participants & organizers to the provisionof laws and regulations